Plasmodium falciparum-CD36 Structure-Function Relationships Defined by Ortholog Scanning Mutagenesis. (18th October 2018) - Cabrera, Ana; Neculai, Dante; Tran, Vanessa; Lavstsen, Thomas; Turner, Louise; Kain, Kevin C
Abstract : Using the structure of h CD36, CIDRα binding peptides, and the differential binding of CD36 orthologs to Plasmodium falciparum -infected erythrocytes (IEs), we investigated how the structure of h CD36 dictates its interaction with intact IEs. Abstract: Background: The interaction of Plasmodium falciparum -infected erythrocytes (IEs) with the host receptor CD36 is among the most studied host-parasite interfaces. CD36 is a scavenger receptor that binds numerous ligands including the cysteine-rich interdomain region (CIDR)α domains of the erythrocyte membrane protein 1 family (PfEMP1) expressed on the surface of IEs. CD36 is conserved across species, but orthologs display differential binding of IEs. Methods: In this study, we exploited these differences, combined with the recent crystal structure and 3-dimensional modeling of CD36, to investigate malaria-CD36 structure-function relationships and further define IE-CD36 binding interactions. Results: We show that a charged surface in the membrane-distal region of CD36 is necessary for IE binding. Moreover, IE interaction with this binding surface is influenced by additional CD36 domains, both proximal to and at a distance from this site. Conclusions: Our data indicate that subtle sequence and spatial differences in these domains modify receptor conformation and regulate the ability of CD36 to selectively interact with its diverse ligands.